Hambatan Didaktis Siswa SMP dalam Penyelesaian Masalah Geometri Berdasarkan Kemampuan Persepsi Ruang - Nurjanah, Nurjanah; Juliana, Anggi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2020)
This study aims to produce a description of students' didactical obstacles in solving geometric problems based on their spatial perception ability. Didactical obstacles were obtained through the results of the analysis of the students' spatial perception obtained ability from the test of geometric instruments associated with the spatial perception ability. This research method is descriptive qualitative. The participants of this study were junior high school students and mathematics teachers. The analysis of the students' spatial perception ability was obtained based on the results of instrument tests, in-depth interviews, and document analysis. The results of this study showed that most students experienced didactical obstacles in solving geometric problems based on their spatial perception ability.Penelitian ini bertujuan untuk menghasilkan gambaran dari hambatan didaktis siswa dalam penyelesaian masalah geometri berdasarkan kemampuan persepsi ruang. Hambatan didaktis diperoleh melalui hasil analisis dari kemampuan persepsi ruang siswa yang diperoleh dari uji instrumen geometri yang dikaitkan dengan kemampuan persepsi ruang. Metode penelitian ini adalah kualitatif deskriptif. Partisipan penelitian ini adalah siswa SMP dan guru matematika. Analisis kemampuan persepsi ruang siswa diperoleh berdasarkan hasil uji instrumen, wawancara yang mendalam, dan analisis dokumen. Hasil penelitian ini menunjukkan sebagian besar siswaÂ  mengalami hambatan didaktis dalam menyelesaikan masalah geometri berdasarkan kemampuan persepsi ruang.